2001
DOI: 10.1097/00000542-200108000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Perioperative Adverse Respiratory Events in Children with Upper Respiratory Tract Infections

Abstract: The current study identified several risk factors for perioperative adverse respiratory events in children with lulls. Although children with acute and recent URIs are at greater risk for respiratory complications, these results suggest that most of these children can undergo elective procedures without significant increase in adverse anesthetic outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
207
6
28

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 383 publications
(250 citation statements)
references
References 18 publications
9
207
6
28
Order By: Relevance
“…In a large trial by Tait et al, 4 the total airwayrelated complication rate was 30% in children with actual URI and 25% in those with a recent history of URI. In another study, von Ungern-Sternberg et al 17 reported a complication rate of 19% in non-URI patients and nearly 32% in URI patients.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…In a large trial by Tait et al, 4 the total airwayrelated complication rate was 30% in children with actual URI and 25% in those with a recent history of URI. In another study, von Ungern-Sternberg et al 17 reported a complication rate of 19% in non-URI patients and nearly 32% in URI patients.…”
Section: Discussionmentioning
confidence: 96%
“…According to the available literature, severe or sustained postoperative coughing in patients with active URI occurs in 4-15% of patients. 4,17 However, severity of coughing as well as occurrence of other airway complications are rather subjective parameters with a marked inter-observer variation. Thus, rather than including only ''severe'' events, we chose to record the incidence of these events regardless of severity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These cohorts suggest a two-to threefold increase in the RR of transient desaturation in the perioperative period. 62,[65][66][67] Desaturation was variably defined as saturations < 95% to < 90%. A single study that distinguished minor desaturations (# 95%) from major desaturations (# 85%) found no association between URI and the more significant events.…”
Section: Is the Child With Uri At An Increased Risk Of Perioperative mentioning
confidence: 99%